2020
DOI: 10.2118/200581-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Multisolution Optimization Framework for Well Placement and Control

Abstract: Summary Field development and control optimization aim to maximize the economic profit of oil and gas production. Mathematically, this results in a complex optimization problem with a large number of correlated decision (also known as control) variables of various types at different levels (e.g., at the level of well location variables or at the level of well production/injection control also know as well control or control settings variables) and a computationally expensive objective function (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In addition, clustering has been usually adopted for determining the representative set of samples for realization. Also, the Net Present Value (NPV) is usually taken as an objective function (Jesmani et al 2020;Salehian et al 2021aSalehian et al , 2021bSalehian et al , 2020Chen et al 2012;Shirangi and Durlofsky 2016;Wang et al 2012;Sefat et al 2016;Moraes et al 2019;Mohsin Siraj et al 2017;Brito and Durlofsky 2021;Lu and Reynolds 2020;Fonseca et al 2020).…”
Section: Recent Advances In Unconventional Resources Development Optimizationmentioning
confidence: 99%
“…In addition, clustering has been usually adopted for determining the representative set of samples for realization. Also, the Net Present Value (NPV) is usually taken as an objective function (Jesmani et al 2020;Salehian et al 2021aSalehian et al , 2021bSalehian et al , 2020Chen et al 2012;Shirangi and Durlofsky 2016;Wang et al 2012;Sefat et al 2016;Moraes et al 2019;Mohsin Siraj et al 2017;Brito and Durlofsky 2021;Lu and Reynolds 2020;Fonseca et al 2020).…”
Section: Recent Advances In Unconventional Resources Development Optimizationmentioning
confidence: 99%
“…Initial sensitivity analysis in this work showed that more stable search process and faster convergence is achieved when 𝛼 0 = 0.5 and 𝑐 𝑚𝑖𝑛 = 0.08 for both well location and control optimization. Detailed information about SPSA formulation for well placement and control optimization can be found in Salehian et al (2020a). The following constraints are applied to control variables during each optimization level:…”
Section: Problem Formulationmentioning
confidence: 99%
“…• Well locations are maintained within the actual, irregular reservoir boundary limits, represented by a binary matrix with 0 and 1 elements indicating null and active reservoir grids, respectively. Following Salehian et al (2020a), each well is moved to the nearest active grid if it appears outside the reservoir boundaries during location optimization.…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations